Diffusion with irregular drift in a Hilbert space - Osipchuk, M. M. (Ukrains’kyi Matematychnyi Zhurnal, 1995)
We construct a generalized diffusion process in a separable Hilbert space. The drift of this process satisfies certain conditions of integrability with respect to the Gaussian measure. We establish the properties of the constructed process.